Dialogic Interactions in two Chamber Music with Guitar from Mikhail Bakhtin (Orfeu, 2025)
This work brings reflections on chamber music with guitar extracted from concepts related to discursive polyphony (or heterodiscourse) by the Russian linguist and philosopher Mikhail Bakhtin. Here we relate the concept of dialogical interaction in the preparation for the musical performance of the works Toccata Polkeada, by Cyro Delvizio for guitar quartet, and the second movement of Na-Yucat VI, written by composer Roberto Victorio for cello and guitar. To analyze the heterodiscursive dynamics in the aforementioned specific repertoire, Bakhtin's theory of dialogism is applied, highlighting the interaction between composer, performers and the musical instruments themselves. Within discursive polyphony, three categories are presented: hybridization, interillumination and confrontation. These categories are appropriate for constructing the performance of a work, where interactions, intricate or not, rarely resort to traditional categories such as accompaniment or main line. Through the application of Bakhtinian concepts of dialogical polyphony and its interaction models, strategies and procedures adopted by interpreters are proposed to promote expressive and cohesive interactions in the investigated chamber groups and in the works. The results point to the importance of dialogue and interaction between musicians in creating a coherent and authentic musical expression.
Keywords: chamber music; chambers’s interaction; dialogism in music; interactions modalits; discursive poliphonic